(untitled) (Per Musi, 2015)
The music scene in the city of Belo Horizonte, capital of Minas Gerais, Brazil, has its production characterized by great diversity, creative quality, innovation and growing dynamism. Would these ingredients be sufficient to consider the possibility of building a Local Production and Innovation System (SPIL by short) of music in this city? This question led to a discussion about the existing conditions or those that need to be created so that this system could be organized. Accordingly, we analyzed the factors that may facilitate or prevent such construction.